2018
DOI: 10.1242/jeb.187740
|View full text |Cite
|
Sign up to set email alerts
|

How does the environment affect fighting? The interaction between extrinsic fighting ability and resource value during contests

Abstract: An individual's performance during a fight is influenced by a combination of their capacity and willingness to compete. While willingness to fight is known to be determined by both intrinsic and extrinsic drivers, an individual's capacity to fight is generally thought of as solely intrinsic, being driven by a host of physiological factors. However, evidence indicates that variation in fighting ability can also be generated through exposure to different environmental conditions. Environmental contributions to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…The value of the resource could be determined by satiation state (i.e., if the resource is food), mating history or predatory abundance (i.e., for shelters) (Arnott & Elwood, ; Enquist & Leimar, ; Maynard Smith, ; Maynard Smith & Parker, ). The perceived value of a resource can interact with intrinsic fighting ability to drive contest dynamics (Lane & Briffa, ). In addition, early environmental influences as well as experience in social situations also play a role in fight dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of the resource could be determined by satiation state (i.e., if the resource is food), mating history or predatory abundance (i.e., for shelters) (Arnott & Elwood, ; Enquist & Leimar, ; Maynard Smith, ; Maynard Smith & Parker, ). The perceived value of a resource can interact with intrinsic fighting ability to drive contest dynamics (Lane & Briffa, ). In addition, early environmental influences as well as experience in social situations also play a role in fight dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of public and private information by an individual is a spectrum, and the position some individual holds is dependent on resource value and predation risk. Indeed, recent work concluded that there is an increasing need to combine intrinsic (e.g., RHP or size) and extrinsic conditions (e.g., resource abundance) to create a more complete view of fighting behaviours (Lane & Briffa, ).…”
Section: Discussionmentioning
confidence: 99%
“…forage quality), and intrinsic factors related to the subjective value an individual assigns to the resource (i.e. mating opportunity) (Enquist & Leimar, 1987;Lane & Briffa, 2018). Accordingly, as the value of the resource increases, so does the cost that an animal is willing to pay for that resource, for example, in terms of contest duration or energy allocation (Arnott & Elwood, 2008;Enquist & Leimar, 1987;Maynard Smith, 1982).…”
Section: Aggressive Interactions At the Group Levelmentioning
confidence: 99%
“…male age) and extrinsic (e.g. size and quality of the territory assessed by measuring other attributes such as fibre content or crude protein) factors influencing value of resources (Lane & Briffa, 2018) in territorial male guanacos is needed to better understand potential impacts on aggressive behaviour.…”
Section: Aggressive Interactions At the Group Levelmentioning
confidence: 99%
“…The possibility that habitat alteration influences the composition of available mates is especially likely in species where resources have to be competed for and monopolised for individuals to be able to attract mates. Environmental factors are known to influence the outcome of competition for resources in general, and the effect can even be larger than the effect of intrinsic properties of individuals (Lane and Briffa 2018). In support of an effect of environmental conditions on the competition for resources needed in mate attraction, a few studies find changes in the environment to alter the number of individual monopolising resources and, thus, being available as mates (Candolin and Vlieger 2013, Candolin et al 2014, Ryder and Sillett 2016).…”
Section: Introductionmentioning
confidence: 99%